Brides for sale: Cross-border marriages and female immigration - Daiji Kawaguchi; Soohyung Lee (Institute for the Study of Labor (IZA), 2012)
Every year, a large number of women immigrate as brides from developing countries to developed countries in East Asia. This phenomenon virtually did not exist in the early 1990s, but foreign brides currently comprise 4 to 35 percent of newlyweds in these developed Asian countries. This paper argues that two factors account for this rapid increase in bride importation: the rapid growth of women's educational attainment and a cultural norm that leads to a low net surplus of marriage for educated women. We provide empirical evidence supporting our theoretical model and its implications, using datasets from Japan, Korea, Singapore, and Taiwan.
urn:nbn:de:101:1-201208065409
Keywords: A12; J12; J61; 330; immigration; marriage; sex ratio imbalance; international marriages; cross-border marriages; assortative matching; Internationale Wanderung; Frauen; Ehe; Bildungsniveau; Brain Drain; Familienökonomik; Japan; Südkorea; Taiwan; Singapur